Perinatal programming of hypertension: Does low maternal dietary salt intake during pregnancy and lactation plays a role in the offspring's blood pressure? - Mohd Noor, Noriah (2018)
Perinatal programming is a concept whereby adverse condition in utero or early postnatal life environment may contribute to chronic diseases in the adult offspring. General consensus mainly agrees that high dietary salt consumption is linked to the development of hypertension and salt restriction lowers blood pressure. However, with regards to intrauterine environment, the effects of salt intake by mothers on the fetal growth may be different. Inconsistent results have been reported in the studies done on the effects of maternal salt intake in the offspring’s blood pressure. The differences in timing and duration of these prenatal insults also contributed to these discrepancies. In this studies, we investigate the effects of high and low maternal dietary salt intake on their offspring’s blood pressure at 12 weeks. Normotensive female rats were subjected to timed pregnancy. Pregnant rats were randomly divided into three groups and were fed either low-sodium diet (LSD) (0.145%NaCl) (n=10), normal-sodium diet (NSD) (1.0%NaCl) (n=10) or high-sodium diet (HSD) (3.0%NaCl)(n=10) during pregnancy and 4 weeks of lactation. The offsprings were weaned at 4 weeks old. The birth weight of male offspring from dams on low salt diet (LSD, 0.145%) were significantly lower than normal salt diet (NSD, 1%) dams ( 5.91g± 0.08 vs 6.29g ± 0.07)( P< 0.05). The total glomeruli number were much lower in the offspring from LSD and HSD dams than in NSD dams (8080.50 ± 706.49 vs 5256.50 ± 867.78 vs 11300.83 ± 1041.72)( P< 0.05), respectively). There was also evidence of haemorrhages in the glomerular tuft and interstitium in the offsprings from HSD and LSD dams. Both high (3% NaCl) and low (0.145% NaCl) salt diet offsprings have greater propensity to develop higher systolic blood pressure in later life (137.29 mmHg ± 1.41 vs 128.77 mmHg ± 1.77 and 134.71mmHg ± 1.13 vs 128.77mmHg ± 1.77) (P< 0.05) respectively . High and low maternal salt intake during pregnancy resulted in abnormal renal development of the offspring. The interruption of normal kidney morphogenesis resulted in a reduced number of nephrons and aberrant development of the kidney. The abnormal renal structures might predispose both LSD and HSD offsprings to develop hypertension in later life. Hence, the insult in utero environment may predispose or “program” an individual to an increased risk of developing renal or cardiovascular disease in later life. The benefits of salt restriction have been assume and there is no knowledge of how far the salt restriction should go. This suggests the importance of maternal dietary salt optimization.